Analysis of Estimated Deaths from Hypertension in Pregnant Women and Population Aged ≥15 Years by Gender in Central Kalimantan Province in 2021 - Pitrah Asfian; Windi Wulandari; Wa Ode Siti Nurfauzah; Zahra Sa'ada Fatiyyah Tanzil; Wulan Sagitat Aprilianti; Wa Ode Aurela Utami Putri Djumain; Yuliana Safitri (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Hypertension is one of the most prevalent non-communicable diseases and a leading contributor to global mortality. It significantly increases the risk of cardiovascular complications, including stroke and heart disease, and adversely affects quality of life. In Indonesia, including Central Kalimantan Province, hypertension represents a major public health concern, with a consistently increasing trend in both prevalence and hypertension-related mortality. According to the 2021 Central Kalimantan Provincial Health Profile, hypertension ranks among the five leading causes of death, particularly affecting individuals of productive age, the elderly, and pregnant women. These groups require targeted and sustained interventions to prevent adverse outcomes. Objective: This study aims to analyze the estimated number of hypertension cases and related deaths among individuals aged ≥15 years and pregnant women in Central Kalimantan Province in 2021, stratified by sex. Methods: A quantitative descriptive study was conducted using secondary data obtained from the 2021 Central Kalimantan Provincial Health Office Profile. Data were analyzed narratively to describe the distribution of hypertension cases and mortality patterns across districts. Results: The analysis identified 646,208 individuals aged ≥15 years diagnosed with hypertension, with the highest case burden observed in Kapuas Regency and Palangka Raya City. Overall, hypertension prevalence was higher among men, although higher proportions among women were observed in selected districts, including East Kotawaringin and Lamandau. Hypertension-related mortality among pregnant women was highest in Kapuas Regency. Health promotion interventions and the utilization of complementary approaches, such as red ginger and cucumber consumption, demonstrated potential benefits in reducing hypertension risk. Conclusion: Effective hypertension management in Central Kalimantan requires comprehensive and gender-sensitive strategies, particularly for vulnerable populations. Education-based interventions and complementary therapies may serve as supportive preventive measures.